The equine herpesvirus-1 (EHV-1) IR3 transcript downregulates expression of the IE gene and the absence of IR3 gene expression alters EHV-1 biological properties and virulence - Ahn, Byung Chul (2010)
The IR3 transcript of equine herpesvirus-1 (EHV-1) harbors 117 nts antisense to the immediate-early (IE) mRNA, suggesting it plays a regulatory role. Here, we show that the IR3 transcript downregulates IE gene expression and that the absence of IR3 expression altered EHV-1 biological properties and virulence in mice. Reporter assays revealed that the IR3/IE overlapping sequences [IR3(+226/+342)] and an additional IR3(+343/+433) region are necessary for the IR3 RNA to downregulate IE expression. Experiments with the ΔIR3 EHV-1 showed that the IR3 gene is dispensable for EHV-1 replication. Protein expression of the IE and representative EHV-1 genes was increased in cells infected with ΔIR3 EHV-1 as compared to that of cells infected with wt EHV-1. The ΔIR3 EHV-1 exhibited increased virulence in mice as compared to the parent virus. The finding that the IR3 transcript affects IE gene expression extends the role of RNA as a regulatory molecule in alphaherpesvirus infection.